The Effect of Growth Medium pH towards Trypsin-Like Activity Produced by Lactic Acid Bacteria - DYAH WULANSARI; BUDIASIH WAHYUNTARI; TRISMILAH TRISMILAH; ASTUTIATI NURHASANAH (Indonesian Society for microbiology, 2012)
In cases of pancreatic disease, trypsin deficiency often occurs due to reduced expression of trypsin in the pancreas. Patients with pancreatic problem can be treated with a supplement containing digestive enzymes, including trypsin. However, most of the enzymes currently used for the treatment are derived from porcine and bovine sources. On the other hand, lactic acid bacteria are also known to show trypsin-like activity. In the previous work, our group screened 11 lactic acid bacteria isolates, which had previously been proven to show serine protease activity, for trypsin-like activity. The strains were initially grown in MRS (de Mann, Rogosa and Sharpe) medium before being transferred directly to the production medium to produce trypsin. During the previous study, the initial pH of the production medium was set at 6 (the same as the MRS medium pH), which is the optimum pH for the cell growth of lactic acid bacteria. However, most trypsin has an optimum pH of around 8. In this study, we altered the production medium pH to 8 and we harvested the lactic acid bacteria from MRS medium by centrifugation prior to their inoculation to the production medium. Observation of the culture growth and enzyme activity indicated that the new strategy improved the enzyme activity expressed by some strains.